The intellectual phase of manual training - Robertson, Kate L. (My University, 1905)
Introduction: Today we find instruction in manual training in some form or other introduced into the schools of most of our progressive cities. It has not come like many educational fads which are of a short duration but has established its value in developing the powers of observation, in calling for, the use of judgment in much the same manner as that of the teaching of the sciences. Arguments have been advanced in favor of manual training from three standpoints - namely that of the pedagogue, the sociologist and the utilitarian. The utilitarian and sociological benefits of education in manual training were earliest reasons advanced in favor of such instruction but it remained for the pedagogue to advance the strongest arguments for such education, arguments that will hold good for all time. Let us glance briefly at the sociological and utilitarian standpoints before taking up that of the pedagogue. Prom the sociological standpoints the new education has been looked upon with favor. The sociologist has discovered that it promotes the growth of the child both individually and in a social way. “The girl who has learned the theory and practice of cooking and who can make her own garments will be a more sympathetic and tolerant woman because of such knowledge and skill.” The boy who studies the classics it has as much need, physiologically and psychologically, of this training as has the boy who must earn his own living, and society is equally concerned with both cases.
Citation: Robertson, Kate L. The intellectual phase of manual training. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Manual Dexterity; Subject's Aim Development of Habits; Repetition is Corner Stone of Development; Theses